Balancing Formality and Informality in Business Exchanges as a Duality: A Comparative Case Study of Returnee and Local Entrepreneurs in China. (5th June 2015) - Lin, Daomi; Lu, Jiangyong; Li, Peter Ping; Liu, Xiaohui
ABSTRACT The management paradigms in the West mainly rely on legal contracts and explicit rules (formality), while the management traditions in the East emphasize social relationships and implicit norms (informality). In an era of 'West-meets-East', balancing formality and informality is becoming critical for firms, especially those facing institutional differences in transnational contexts and institutional transitions. In this research, we conducted a comparative multicase study on returnee entrepreneurs and local entrepreneurs in China. We found that at the early stage of venturing, returnee entrepreneurs emphasized formality more than informality, while local entrepreneurs stressed informality more than formality. However, the formality-informality balance among both returnee and local entrepreneurs converged over time in line with the institutional transition in China. Returnee entrepreneurs increased the emphasis on informality (but kept the dominant position of formality), whereas local entrepreneurs gradually shifted from informality to formality. The spatial pattern of asymmetrical balancing and the temporal pattern of transitional balancing are both rooted in the Chinese philosophy of Yin-Yang balancing.